Competing social identities and intergroup discrimination: Evidence from a framed field experiment with high school students in Vietnam - Tam Kiet Vuong; Ho Fai Chan; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
We conducted a framed field experiment to explore a situation where individuals have potentially competing social identities to understand how group identification and socialization affect ingroup favoritism and out-group discrimination. The Dictator Game and the Trust Game were conducted in Vietnam's Ho Chi Minh City on two groups of high school students with different backgrounds, i.e., French bilingual and monolingual (Vietnamese) students. We find strong evidence for the presence of these two phenomena: our micro-analysis of within- and betweenschool effects show that bilingual students exhibit higher discriminatory behavior toward nonbilinguals within the same school than toward other bilinguals from a different school, implying that group identity is a key factor in the explanation of intergroup cooperation and competition.
Keywords: C93; C70; D74; 330; socialization; in-group favouritism; out-group discrimination; cooperation; trust; trustworthiness; fairness; altruism; risk preference